Kepemimpinan Spiritual Founder Yayasan Indonesia Bershalawat Kediri - Puspita, Maulidiyah Ayu; Hakim, Ahmad Khairul (Journal of Islamic Management, 2025)
This study aims to analyse the spiritual leadership of the founder of Indonesia Bershalawat Kediri Foundation and to analyse the impact of the application of spiritual leadership. To analyse these issues, the researcher used qualitative research methods by using data triangulation techniques through interviews, observation, and documentation. The results of this study are the leadership applied at the Indonesia Bershalawat Foundation, the founder of the Indonesia Bershalawat Foundation uses a spiritual leadership style with attitude values in spiritual leadership according to Fry's theory, namely vision, altruistic, and hope/faith. Vision is realised by an understanding of the vision, a vision statement, inspiration from the vision, and a clear vision. Altruistic is manifested by leaders and followers showing care, working as discussed, being honest, trusting and loyal, courageous and caring. Hope/faith is manifested by having faith, carrying out beliefs, persevering, making more effort, and challenging goals in their vision will be passionate in the face of obstacles, enduring difficulties and suffering in achieving their goals. However, in this case, researchers found a character trait that is not found in the theory, namely firmness but compassion. In addition, the impact of the spiritual leadership of the founder of the Indonesia Bershalawat Foundation provides spiritual well being which includes calling and membership. There are several indicators of calling, namely the importance of work for the person, the meaning of work for his life and the statement that work makes a difference in life. While membership indicators are feeling understood in the organisation, feeling valued in the organisation, feeling valuable in the organisation, feeling respected in the organization.